THE THE PREJUDICAL QUESTION AS A SECONDARY SUBJECT OF AN ADMINISTRATIVE PROCEDURE - Stevandić, Danilo (Pravni zapisi, 2022)
The prejudicial question is a disputable (unresolved) legal issue which, as an independent legal issue, represents the subject of either court or other administrative procedure, and whose resolution decisively affects the decision on an administrative matter and thereby represents a secondary subject of an administrative procedure. The legal term “preliminary question” is not synonymous with the legal term “prejudicial question”, and the term “incidental question” may be synonymous with it when used in a narrower sense. A prejudicial question acts as a factual issue in administrative proceedings since it is an element of the factual situation, even though it always represents a legal issue in its nature. The Republic of Serbia has been implementing a combined model with regards to resolving the prejudicial question, according to which the administrative body, except for cases prescribed by law, may choose to either consider and independently discuss the prejudicial question or terminate the proceedings until the court or other competent authority resolves the issue. The novelties introduced in the General Administrative Procedure Act (2016) limit the powers of administrative bodies in resolving prejudicial issues and thus create conditions for more consistent implementation of both the principle of separation of powers and rules on absolute incompetence in matters of great importance for the rights of individuals and the society as a whole.